Bio-SiC ceramics coated with hydroxyapatite using gas-detonation deposition: An alternative to titanium-based medical implants - Klyui, M.I.; Temchenko, V.P.; Gryshkov, O.P.; Dubok, V.A.; Kladko, V.P.; Kuchuk, A.V.; Dzhagan, V.M.; Yukhymchuk, V.O.; Kiselov, V.S. (Functional Materials, 2013)
Silicon-carbide (SiC) ceramics synthesized using forced infiltration and coated with bioactive hydroxyapatite (HA), represents a great potential for replacement of traditional titanium medical implants. In this paper the surface morphology, structural properties and phase content of HA coatings deposited onto nano-porous bio-SiC ceramics with pore orientation being parallel or perpendicular to the plain of subsequently deposited HA film have been studied. The HA coatings produced at 5 s of deposition contained cracks, while the uniform hydroxyapatite coating has been produced at 10 s of deposition. X-ray diffraction analysis revealed that the HA coatings preserve crystal structure of the initial hydroxyapatite powder during deposition. From the intensity ratio of Raman scattering peaks, corresponding to crystalline (967 cm⁻¹) and amorphous (951 cm⁻¹) HA, the least and most crystalline structures were found. The structural perfection of the HA coating was higher for SiC substrates with parallel pore orientation (with respect to the plane of HA growth), indicating that structural properties of SiC ceramics affect the morphological and structural perfection of deposited HA coating.